Strategy for Improving Household and MSMEs Financial Management Towards Financial Independence for the Mijen Community - Rita Rosalina; Muhammad Ja'far Shodiq; Khansa Shabihah; Nur Hidayah Cahya Putri (LPPM Universitas Islam Sultan Agung, 2026)
Financial independence is a crucial factor in improving community welfare, particularly for households and MSMEs in developing areas such as Mijen Village. This study aims to analyze changes in community financial literacy and management skills before and after participation in a financial education program. The method used was participatory action research with pre-test and post-test instruments to evaluate changes in participants' understanding. Primary data were collected through questionnaires covering aspects of budget planning, financial record-keeping, cash flow management, and the separation of household and business finances. The results showed significant improvements in most indicators after the educational intervention. Respondents who initially had only a moderate understanding of financial management showed improvement, as evidenced by increases in average post-test scores across both conceptual understanding and the application of financial practices. MSMEs and households began to implement savings strategies, manage cash flow more discipline, and maintain a more apparent financial separation. The results of this study confirm that the financial literacy-based empowerment program is effective in increasing community financial independence and supporting local economic sustainability in Mijen Village.